Polymer Composites for Electromagnetic and Electrostatic Shielding - Pietrzak, Łukasz; Stano, Ernest; Szymański, Łukasz (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The article describes electromagnetic shielding capabilities of carbon nanotube polymer and multiwalled carbon nanotube nanocomposites obtained by spray – drying technique. The used method guarantees uniformly dispersed carbon nanotubes (CNTs), what resulting in forming the continuous network of CNTs inside the polymer matrix. The technique also allows working with solution that is the basis of homogeneous composite material preparation, as the agglomeration of the filler destroys the material desired electromagnetic shielding properties. In manufactured nanocomposites network of conductive filler is playing the role of the electromagnetic radiation shield and thus it is so important to develop the highly effective preparation method leads to uniform dispersion of the filler. Another important feature of the examined nanocomposites is electrostatic shielding capability based also on good uniform carbon nanotubes dispersion what makes the outcome material suitable for protecting fragile electronic devices. The filler particles used in the described process are multiwalled carbon nanotubes coming from LSCVD synthesis in our own laboratory. In this article we are introducing both the method and results for the first of filler and polymer as the basis for the future work we want to finally present.